An experimental investigation on the effect of feedback control policy and need for achievement on subordinates’ budgetary slack creation / Vincent K. Chong and Irdam Ferdiansah - K., Vincent Chong; Ferdiansah, Irdam (Accounting Research Institute (ARI), 2012)
This paper examines the effects of one management control mechanism - namely, feedback control policy - on subordinates’ budgetary slack creation. This paper also investigates the interaction effect of feedback control policy and the personality trait of ‘need for achievement’ on budgetary slack. A laboratory experiment was conducted and a 2x2 analysis of variance (ANOVA) was used to test the hypotheses formulated for this study. The independent variables were the feedback control policy and the personality trait of ‘need for achievement’. The dependent variable was budgetary slack. The results indicate that the presence of a feedback control policy reduces the budgetary slack created by managers under private information conditions. The results further reveal that managers with a high need for achievement create less budgetary slack than those with a low need for achievement, when feedback control policy exists.